Pengaruh Work Family Conflict, Kepemimpinan Transformasional dan Kompleksitas Tugas Terhadap Job Satisfaction - Wilda Farah (Department of Accounting-Faculty of Economic and Business (FEB), 2017)
This research was aimed to examine the influence of work-family conflict, transformational leadership, and task complexity on job satisfaction. This research used primary data which collected by distributing questionnaires to respondents. Questionnaires were distributed to leader, junior and senior auditor of Internal Control Board (SPI) on State Islamic Higher Education was held BLU status on Ministry of Religious. From 30 questionnaires that have been distributed, all questionnaires have been received an could be processed. The research uses multiple regression analysis method. The results of this research show that: (1) work-family conflict has no significant influence on job satisfaction. (2) Transformational leadership style has significant influence on job satisfaction. (3) task complexity has no significant influence on job satisfaction. (4) work-family conflict, transformational leadership style, and task complexity have significant influence on job satisfaction.